Extending CSP with tests for availability - Lowe, G (2009)
We consider the language of CSP extended with a construct that allows processes to test whether a particular event is available (without actually performing the event). We present an operational semantics for this language, together with two congruent denotational semantic models. We also show how this extended language can be simulated using standard CSP, so as to be able to analyse systems using the model checker FDR. Copyright © 2009 The authors and IOS Press.